Early Human Settlement of Northeastern North America. (2nd July 2016) - Lothrop, Jonathan C.; Lowery, Darrin L.; Spiess, Arthur E.; Ellis, Christopher J.
Abstract : This paper summarizes current evidence for earliest human occupation of northeastern North America during the late Pleistocene and early Holocene. We review evolution of the region's landscapes and evidence of archaeological chronologies as context for understanding human settlement of the region. Current data support limited evidence for pre-Clovis occupation south of the Laurentide glacial margin, followed by a significant temporal gap prior to early Paleoindian settlement of the region. Despite differences in sub-regional data sets, mapping of site distributions and assemblage data do support the notion of variation in lifeways between Paleoindian populations occupying formerly glaciated parts of the Northeast in the late Pleistocene, versus contemporary groups in lands south of the Laurentide glacial margin. Through time, the greatest differences in Paleoindian land use and technology occur between the Younger Dryas and early Holocene.